Barriers to technological innovation of SMEs in Cameroon - Tafor, Melody (2020)
Cameroon is amongst the low- and middle-income economies which have currently acknowledged the advantages of technological innovation although technological transfer (TT) is disrupted by many barriers. This research illustrates the main obstacles to technological innovation and transfer (such as product and process innovation) in Cameroon utilising Technology Innovation theory and Technology Transfer paradigm (TT) and other related literature.